2022
DOI: 10.1111/trf.17145
|View full text |Cite
|
Sign up to set email alerts
|

RHD genotyping to resolve weak and discrepant RhD patient phenotypes

Abstract: Background: We instituted RHD genotyping in our transfusion service for obstetrical patients and transfusion candidates. We sought to examine how RHD genotyping resolved weak or discrepant automated microplate direct agglutination (MDA) RhD phenotypings and impacted needs for Rh Immune Globulin (RhIG) and D-negative RBCs.Study Design and Methods: We investigated RhD phenotypes with equivocal or reagent-discrepant automated MDA (Immucor, Norcross, GA), weak-2+ immediate-spin tube typings, historically discrepan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
0
9
1
Order By: Relevance
“…0.28% of our patients had ambiguous results in serologic RHD‐testing, 0.26% of those due to an aberrant, weak or partial, RHD variant. This was higher than in another, recently published study, investigating an ethnic more diverse population with a prevalence of RHD variants of 0.14% 14 but lower than that reported for Denmark (0.6% and 0.7%), 15,16 a country directly neighboring the region where our patients are originating from. Reasons might be different study protocols, a different sensitivity in the assays, 17 and the experience of the investigators, who observed the test results.…”
Section: Discussioncontrasting
confidence: 72%
“…0.28% of our patients had ambiguous results in serologic RHD‐testing, 0.26% of those due to an aberrant, weak or partial, RHD variant. This was higher than in another, recently published study, investigating an ethnic more diverse population with a prevalence of RHD variants of 0.14% 14 but lower than that reported for Denmark (0.6% and 0.7%), 15,16 a country directly neighboring the region where our patients are originating from. Reasons might be different study protocols, a different sensitivity in the assays, 17 and the experience of the investigators, who observed the test results.…”
Section: Discussioncontrasting
confidence: 72%
“…As kindly cited by Juhl et al, our group previously reported in TRANSFUSION our 2.5-year experience (2019-2021) with RHD genotyping for weak or discrepant patient RhD phenotypes in an American academic medical center serving a diverse urban community. 5 Our serological and RHD genotyping criteria and methods and our management of Rh immune globulin and D-negative transfusions were described. We also routinely performed Rh CcEe phenotypes by tube method (Gamma-clone, Immucor, Norcross, GA) in these patients.…”
Section: Weak or Discrepant Rhd Phenotypes: Laboratory Management Str...mentioning
confidence: 99%
“…We managed type 4.0 patients as D-negative for transfusion unless they had difficult antibodies or high blood needs. 5 Nine of 16 C+ patients (56%) with type 4.0 or other partial RHD variants expressed a partial C phenotype from the hybrid variant RHD*03N (RHDIIIa-CE(4-7)-D) (3N).…”
Section: Weak or Discrepant Rhd Phenotypes: Laboratory Management Str...mentioning
confidence: 99%
“…Weak or discrepant RhD phenotypes occur in 0.1%–0.4% of US patients 1–5 . Rates vary greatly by race, for example, 0.1% of Whites and 0.6% of Blacks in our Chicago obstetrical service 1 .…”
Section: Introductionmentioning
confidence: 97%
“…Weak or discrepant RhD phenotypes occur in 0.1%–0.4% of US patients 1–5 . Rates vary greatly by race, for example, 0.1% of Whites and 0.6% of Blacks in our Chicago obstetrical service 1 . The definition of weak D phenotype has expanded from nonreactive by direct agglutination and antiglobulin reactive with IgG antisera to also include weak‐2+ direct agglutination reactions 6,7 .…”
Section: Introductionmentioning
confidence: 99%